Proposal for a cost-effective centrifugal rotary blood pump: design of a hybrid magnetic/hydrodynamic bearing - Hilton, Andrew (2010)
The growing worldwide prevalence of cardiovascular diseases (CVD) such as chronic heart failure (CHF) highlights the need for an effective treatment method. Annually, there are an estimated 17.5 million deaths caused by cardiovascular diseases worldwide, representing 30% of all global deaths; of these deaths approximately 50% are due to CHF [1] and about 80% occur in low- and middle-income countries [2]. If current trends are allowed to continue, by 2015 an estimated 20 million people annually will die from CVD [3]. Each year, only about 3,000 people receive a heart transplant as the only current definitive long-term treatment for end-stage CHF. To compound the severity of the situation, organ donations are decreasing (4). Implantable blood pumps offer an effective treatment to CHF, either as a bridge to transplantation / recovery, or as destination therapy i.e. use of long term mechanical circulatory support in patients with end-stage heart failure without the intention of eventual heart transplantation. With the number of sufferers of CHF rising in both the developed and developing world it becomes pertinent to design a cost effective device.